2015
DOI: 10.2147/opth.s76847
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metamorphopsia in daily life after successful epiretinal membrane surgery and correlation with M-CHARTS score

Abstract: PurposeTo determine the correlation between the changes in metamorphopsia in daily life environment and the M-CHARTS scores after epiretinal membrane (ERM) removal, and to determine the criterion for determining whether clinically significant changes in the metamorphopsia score have occurred in M-CHARTS.MethodsWe studied 65 eyes undergoing vitrectomy for unilateral ERM. Self-administered questionnaires were used to examine the metamorphopsia in their daily life. The degree of metamorphopsia was determined by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
2
19
0
4
Order By: Relevance
“…The mean vertical and horizontal scores were 0.59 ± 0.57 and 0.52 ± 0.67, respectively. Kinoshita et al[ 20 ] reported that an M-CHARTS score of 0.3 to 0.5 may be the threshold for detecting patients with symptomatic metamorphopsia in their daily life. Twenty-five (59.5%) eyes in the current study had M-CHARTS scores equal to or lager than 0.5 at baseline (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean vertical and horizontal scores were 0.59 ± 0.57 and 0.52 ± 0.67, respectively. Kinoshita et al[ 20 ] reported that an M-CHARTS score of 0.3 to 0.5 may be the threshold for detecting patients with symptomatic metamorphopsia in their daily life. Twenty-five (59.5%) eyes in the current study had M-CHARTS scores equal to or lager than 0.5 at baseline (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nakagawa et al[ 6 ] reported that the M-CHARTS score was unchanged of 6 months in 12 eyes with acute BRVO. Metamorphopsia due to various diseases has been reported to be decreased as a result of treatment [ 5 , 20 , 24 , 29 ]. However, metamorphopsia from BRVO tends to persist even after complete resolution of the ME.…”
Section: Discussionmentioning
confidence: 99%
“…We did not investigate M-CHARTS before RFPDT because we were unable to assess some patients using M-CHARTS because of central scotoma. The presence of metamorphopsia was defined as a mean M-CHARTS score of �0.5˚at 12 months after RFPDT according to previous reports [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…[3,4] Various vitreoretinal diseases cause metamorphopsia and aniseikonia; these diseases include epiretinal membrane (ERM), macular hole (MH), and rhegmatogenous retinal detachment (RRD). [5][6][7][8][9][10][11][12] Pars plana vitrectomy (PPV) is an effective treatment for these retinal diseases, and recent advances in PPV have led to improvements in anatomical success and postoperative visual acuity; however, metamorphopsia combined with aniseikonia often persists and causes considerable problems.…”
Section: Introductionmentioning
confidence: 99%